Impact of standardized immunophenotyping and MRD monitoring on early mortality reduction in childhood leukemia: a step towards addressing healthcare disparities in vulnerable populations from Southern Mexico - Alfaro-Hernández, Laura; Ramírez-Ramírez, Dalia; Romo-Rodríguez, Rubí; Ayala-Contreras, Karen; del Campo-Martínez, Ángeles; López-Aguilar, Enrique; Flores Lujano, Janet; Allende-López, Aldo; Alarcón-Ruiz, Erika; Banos-Lara, Ma Del Rocio; Casique-Aguirre, Diana; Elizarrarás-Rivas, Jesús; et al. (Frontiers in Oncology, 2025)
BackgroundDespite high cure rates for pediatric B-cell acute lymphoblastic leukemia (B-ALL) in high-income countries, early mortality remains unacceptably high in low- and middle-income countries (LMICs), largely due to limited access to risk-adapted therapy and response monitoring. Southern Mexico, a region marked by socioeconomic vulnerability, is emblematic of this disparity. In 2022 the Childhood Cancer Cytomics Laboratory (CCCL) started the implementation of standardized protocols for immunophenotyping and measurable residual disease (MRD) monitoring of B-ALL patients from this region.ObjectiveTo evaluate the impact of implementing standardized immunophenotyping and MRD monitoring on early mortality in children with B-ALL treated in public hospitals in southern Mexico.MethodsA prospective cohort study was conducted between 2022 and 2024. Before initiating CCCL activities, public hospitals were invited to participate, and standardized protocols for sample collection, handling, and transportation were implemented across all participating sites. A total of 298 children newly diagnosed with B-ALL were enrolled and followed throughout treatment. Patients were stratified based on whether immunophenotyping and MRD monitoring were performed at the CCCL. MRD was assessed at the end of induction (EOI) therapy using standardized EuroFlow-based flow cytometry protocols. Simultaneously, early mortality—defined as death occurring within the first year after diagnosis—was evaluated. Adjusted hazard ratios (aHR) and 95% confidence intervals (CI) were estimated using multivariable Cox regression, with p-values < 0.05 considered statistically significant.ResultsEarly mortality was significantly lower among patients who underwent MRD monitoring at the CCCL (10.8%) compared to those who did not (24.8%, p<0.01). One-year overall survival was also higher in patients evaluated at the CCCL (89.6% vs. 75.2%, p<0.001). In the multivariable Cox regression analysis, patients who underwent MRD monitoring at the CCCL showed a significantly lower risk of early mortality during the first year of treatment (adjusted hazard ratio [aHR] 0.41; 95% CI: 0.22–0.77; p < 0.01), after adjusting for sex, NCI risk classification, treatment abandonment, and early relapse. MRD positivity was associated with a CD34+ ProB immunophenotype, suggesting a more treatment-resistant leukemic profile.ConclusionCentralized, standardized MRD monitoring at the CCCL was associated with a reduction in early mortality and improved one-year survival in children with B-ALL from a socioeconomically vulnerable population. These findings demonstrate the clinical value and feasibility of implementing MRD-informed response assessment in LMICs and highlight the potential of centralized diagnostic platforms to reduce survival disparities in childhood leukemia.